THE PRINCIPLE OF ESP TEACHING: ITS CONCEPT, OBJECTIVES AND COURSE DESIGN - Uyun, Aip Syaepul (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2020)
This article provides a brief description on teaching English for Specific Purposes (ESP) and responses to the issues happening on ESP instruction among foreigner particularly in Indonesia. ESP can be referred to English language teaching for specific career, studies or professionalism. Hence, there is specific reason for which English is learned. The materials and the skills learnt by students are different from General English. As the result, creating an appropriate course design of ESP is also different. Unfortunately, in its implementation, there are still many cases that is not supposed to be happened in ESP learning teaching practice. For instance, in some universities ESP is even practiced like General English. In another cases ESP instruction is even far from the concept of teaching in it. Based on this reason, the writer would like to propose three important items to practice ESP well. It is necessary to the institution, ESP lecturer, and all parties include it, to consider three most important aspects in practicing ESP. Those are ESP concept, ESP objective, and ESP course design. Â Hereinafter, after discussing this principle, there will be no longer available to discuss that the wrong perception in ESP practice still happen in university student.